Teaching Strategy in Islamic Religious Education for Children at Tadika Al-Fikh Orchard Taman Setia Selagor - Rizqi, Rizqi; Setiawan, Hasrian Rudi (Universitas Pahlawan Tuanku Tambusai, 2025)
This study investigates the suboptimal teaching strategies of Islamic religious education at Tadika Al-Fikh Orchard Taman Setia, focusing on their limited effectiveness in sparking children's interest and encouraging active participation. It aims to identify the strategies employed by teachers, explore the challenges they face, and analyze the factors that influence the success of these strategies. Using a descriptive qualitative approach, the research objectively examines the strategies in a natural setting to understand their implementation and impact. The findings reveal that active and collaborative teaching methods contribute to positive behavioral changes in children, such as a greater willingness to apologize and increased confidence in speaking. The success of these strategies is influenced by the emphasis on practical application of Islamic moral values. The study concludes that effective teaching strategies in Islamic education can foster behavioral development and instill noble character in young learners.